The outcomes of Polish patients with advanced BRAF-positive melanoma treated with vemurafenib in a safety clinical trial - Rutkowski, Piotr; Kozak, Katarzyna; Mackiewicz, Jacek; Krzemieniecki, Krzysztof; Nawrocki, Sergiusz; Wasilewska-Teśluk, Ewa; Kwinta, Łukasz; Wysocki, Piotr; Koseła-Paterczyk, Hanna; Świtaj, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: The BRAF inhibitor vemurafenib has improved progression-free survival and overall survival in patients with BRAFV600-mutation-positive metastatic melanoma. Here we present the results of an open-label safety study with vemurafenib in patients with metastatic melanoma enrolled in Polish oncological centres. Material and methods : Patients with untreated or previously treated Stage IIIC/IV BRAFV600 mutation-positive melanoma were treated with oral vemurafenib in an initial dose of 960 mg twice daily. Assessments for safety and efficacy were made every 28 days. For the survival analysis the Kaplan-Meier estimator was used with the log-rank tests for bivariate comparisons. Results : In total, 75 Polish patients were enrolled in the safety study across four centres. At data cut-off, 28 patients died (37%), mainly (26) due to disease progression; 33 (44%) patients continued vemurafenib after disease progression. The objective response rate was 46%, including two patients with a complete response and 29 with a partial response. Median progression-free survival was 7.4 months. The one-year overall survival rate was 61.9% (median overall survival was not reached). Seventy-three (97.3%) patients reported adverse events (AEs), and grade 3–5 toxicity was reported in 49.4% (37) patients. The most common AEs were: skin lesions (including rash and photosensitivity), arthralgia, and fatigue. Conclusions : The overall safety profile and response rate of vemurafenib were comparable to those reported in previous studies of this drug. Our study confirmed the value of well-established prognostic features for overall survival, such as initial LDH (lactate dehydrogenase) level and AJCC staging.